Immobilization following Distal Radius Fractures: A Randomized Clinical Trial - Hill, J. Ryan; Navo, Paul D.; Bouz, Gabriel; Azad, Ali; Pannell, William; Alluri, R. Kiran; Ghiassi, Alidad (Journal of Wrist Surgery, 2018)
Background No consensus exists regarding postoperative splinting position following volar plate fixation of distal radius fractures.Purpose The purpose of this study was to determine whether immobilization in supination would result in superior outcomes compared with no restriction of forearm range of motion.Patients and Methods All patients >18 years of age with distal radius fractures indicated for volar plate fixation were eligible. Exclusion criteria were open fracture and concomitant injury to, or functional deficit of, either upper extremity. Patients were randomized to immobilization in (1) maximal supination with a sugar-tong splint or (2) no restriction of supination with a volar splint. Patient-Rated Wrist Evaluation (PRWE), Disabilities of the Arm, Shoulder, and Hand (DASH) score, and visual analog scale (VAS) score; wrist range of motion; and grip strength were recorded at 2 and 6 weeks postoperatively. A Student's t-test was used to compare mean values of all outcome measures at each time point.Results A total of 46 patients enrolled in the study; 28 were immobilized with a volar splint and 18 were immobilized with a sugar-tong splint. Six-week follow-up data were obtained for 32 patients. There was no significant difference in PRWE, DASH, and VAS scores; or range of motion; or grip strength between the two groups postoperatively.Conclusion Range of motion, grip strength, and patient-rated outcome measures were similar regardless of postoperative immobilization technique in patients with a distal radius fractures stabilized with a volar plate. Surgeons can elect to use the standard-of-care postoperative immobilization modality of their preference following volar plate fixation without compromising short-term return to function.Level of Evidence This is a Level II, therapeutic study.
Keywords: distal radius; immobilization; splint